Taming Parasites by Tailoring Them - Ren, Bingjian; Gupta, Nishith (Frontiers in Cellular and Infection Microbiology, 2017)
The next-generation gene editing based on CRISPR (clustered regularly interspaced short palindromic repeats) has been successfully implemented in a wide range of organisms including some protozoan parasites. However, application of such a versatile game-changing technology in molecular parasitology remains fairly underexplored. Here, we briefly introduce state-of-the-art in human and mouse research and usher new directions to drive the parasitology research in the years to come. In precise, we outline contemporary ways to embolden existing apicomplexan and kinetoplastid parasite models by commissioning front-line gene-tailoring methods, and illustrate how we can break the enduring gridlock of gene manipulation in non-model parasitic protists to tackle intriguing questions that remain long unresolved otherwise. We show how a judicious solicitation of the CRISPR technology can eventually balance out the two facets of pathogen-host interplay.